Finding similarities between software development skills - Koskinen, Kristian (My University, 2023)
As software development becomes an increasingly important part of modern society, understanding the similarities and differences between different software development skills is critical for improving the effectiveness and efficiency of software development teams. In this thesis we explore the use of user skill level data to identify similarities in software development skills. Using data from an application that a company uses to gather information about the competence of their personnel. In this thesis we try to explore the possibility of finding similar skills and measuring this similarity. The initial results from this data do not give clear clusters of similar skills however further processing of this data gives results that hold great potential. By providing a measure of similarity between different skills we can better match candidates to job requirements and training programs improving the overall effectiveness and efficiency of software development teams.
Keywords: semantic search, similarity, software development